2002
DOI: 10.1007/s00228-001-0404-7
|View full text |Cite
|
Sign up to set email alerts
|

No clinically relevant drug interaction between paracetamol and phenprocoumon based on a pharmacoepidemiological cohort study in medical inpatients

Abstract: These results suggest that paracetamol co-administration at a dosage of 2000-2500 mg/day for 3 days has no clinically relevant effects on the anticoagulant effects of phenprocoumon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Most participants did not know which OTC analgesic is safe for patients with OAT and even worse some indicated they would buy aspirin or other OTC NSAIDs. Only 20% were aware that paracetamol (acetaminophen) is considered the safest OTC analgesic for patients on OAT with phenprocoumon [30,31]. This lack of knowledge is particularly worrisome since two thirds of the participants indicated they would not inform pharmacists about concomitant use of OAT when purchasing OTC medication.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants did not know which OTC analgesic is safe for patients with OAT and even worse some indicated they would buy aspirin or other OTC NSAIDs. Only 20% were aware that paracetamol (acetaminophen) is considered the safest OTC analgesic for patients on OAT with phenprocoumon [30,31]. This lack of knowledge is particularly worrisome since two thirds of the participants indicated they would not inform pharmacists about concomitant use of OAT when purchasing OTC medication.…”
Section: Discussionmentioning
confidence: 99%
“…It is of importance to know whether there is an interaction between oral anticoagulation and paracetamol since paracetamol is the first‐line analgesic and antipyretic therapy in patients receiving oral anticoagulation. A recent literature review shows that the methodology used varies widely: retrospective, observational or case–control studies, case reports or experimental studies in healthy subjects suggest the occurrence of an increase in the anticoagulant effect of oral anticoagulation by paracetamol [4, 6–8, 13, 14], while others do not [12, 15, 16]. But all these studies are subject to caution due to methodological biases (retrospective studies, few patients, patients not reflecting those encountered in normal clinical practice) and variable therapies (warfarin but also fluindione, acenocoumarol, phenprocoumon, coumarins).…”
Section: Discussionmentioning
confidence: 99%
“…It is of importance to know whether there is an interaction between oral anticoagulation and paracetamol since paracetamol is the first-line analgesic and antipyretic therapy in patients receiving oral anticoagulation. A recent literature review shows that the methodology used varies widely: retrospective, observational or case-control studies, case reports or experimental studies in healthy subjects suggest the occurrence of an increase in the anticoagulant effect of oral anticoagulation by paracetamol [4, 6-8, 13, 14], while others do not [12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Gingival bleeding and hematuria were observed when paracetamol was given with warfarin (Hylek et al, 1998). Several case reports including case controlled studies have reported that paracetamol potentiates the anti-coagulant effect of warfarin (Andrews, 2002), others have not found a clinically relevant interaction (Fattinger et al, 2002). NSAIDs such as mefenamic acid (Holemes, 1966), etodolac (Ermer et al, 1994), ibuprofen (Penner and Abdrecht, 1975;Schulman and Henriksson, 1989) and tenidap (Apseloff et al, 1995) may also displace coumarin anti-coagulants from protein binding sites.…”
Section: Resultsmentioning
confidence: 99%